How is Mental Illness Discursively Constructed and Conceptualized in a Corpus of Online Blogs? A Corpus-Linguistics Case-Study of Discourses on Mental Illness - Denis Jamet; Christophe Coupé (Anglophonia)
Through a combination of quantitative and qualitative analyses based on corpus linguistics software tools, this article investigates whether the mind / mental self is a brittle object conceptual metaphor enables to conceptualize mental illness in a corpus of American online blogs dedicated to this very topic and, if so, whether the conceptualization is similar for the patients and the professionals and helpers. The quantitative analyses will focus on keywords and relative frequencies and the qualitative analyses on collocations, concordances, semantic prosody and the semantic domains most frequently used to conceptualize mental illness. The study will conclude on the most recurrent conceptual metaphors in the discourses of patients and professionals and helpers and show that, in our corpus, the mind / mental self is a brittle object conceptual metaphor is not frequently used to discursively construct and conceptualize mental illness